99m TcMDP Bone Scan in Lung Cancer: Predilection Sites for Metastasis (Bangladesh Journal of Nuclear Medicine, 2016)
Introduction: Bone scan with 99m Tc-MDP is a commonly used procedure for evaluation of bone metastases because of its high sensitivity, availability, and relatively low cost. The predilection sites for bone metastasis in patients particularly with lung cancers were investigated in this study.Methods: The study was done at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) between January 2013 and June 2014. A total of 123 patients with lung cancers who had whole body scintigraphy with 99mTc-MDP were studied. The bone scans were interpreted by experienced Nuclear Medicine physicians and the predilection sites with pattern of skeletal metastasis were analyzed.Results: Among the 123 (m/f: 104/19) cases studied, 99 (80.5%) patients had bone metastasis. Solitary metastatic lesion was detected in 18.2% cases, multiple lesions in 59.6% cases and extensive metastases were noted in 18.2% cases. Features of hypertrophic pulmonary osteoarthopathy were present in 4% cases. The predilection sites for metastases from lung cancer appear to be in the ribs (75% cases) followed by spines (54% cases) and pelvis (23% cases). In total 595 metastatic lesions were detected, among them 469(78.8%) were distributed in axial skeleton and 126 (21.2%) were in appendicular skeleton. Metastatic involvement was higher in axial skeleton comparing to the appendicular skeleton and the difference was statistically significant (Z=13.99, P